MnSOD is implicated in accelerated wound healing upon Negative Pressure Wound Therapy (NPWT): A case in point for MnSOD mimetics as adjuvants for wound management - Bellot, G.; Dong, X.; Lahiri, A.; Sebastin, S.; Batinic-Haberle, I.; Pervaiz, Shazib; Puhaindran, M. (Elsevier BV, 2019)
© 2018 The Authors Negative Pressure Wound Therapy (NPWT), a widely used modality in the management of surgical and trauma wounds, offers clear benefits over conventional wound healing strategies. Despite the wide-ranging effects ascribed to NPWT, the precise molecular mechanisms underlying the accelerated healing supported by NPWT remains poorly understood. Notably, cellular redox status-a product of the balance between cellular reactive oxygen species (ROS) production and anti-oxidant defense systems-plays an important role in wound healing and dysregulation of redox homeostasis has a profound effect on wound healing. Here we investigated potential links between the use of NPWT and the regulation of antioxidant mechanisms. Using patient samples and a rodent model of acute injury, we observed a significant accumulation of MnSOD protein as well as higher enzymatic activity in tissues upon NPWT. As a proof of concept and to outline the important role of SOD activity in wound healing, we replaced NPWT by the topical application of a MnSOD mimetic, Mn(III) meso-tetrakis(N-ethylpyridinium-2-yl)porphyrin (MnTE-2-PyP5+, MnE, BMX-010, AEOl10113) in the rodent model. We observed that MnE is a potent wound healing enhancer as it appears to facilitate the formation of new tissue within the wound bed and consequently advances wound closure by two days, compared to the non-treated animals. Taken together, these results show for the first time a link between NPWT and regulation of antioxidant mechanism through the maintenance of MnSOD activity. Additionally this discovery outlined the potential role of MnSOD mimetics as topical agents enhancing wound healing.